2019
DOI: 10.1111/jfb.13940
|View full text |Cite
|
Sign up to set email alerts
|

The taste system in fishes and the effects of environmental variables

Abstract: The adaptability of the taste system in fish has led to a large variety in taste bud morphology, abundance and distribution, as well as in taste physiology characteristics in closely related species with different modes of life and feeding ecology. However, the modifications evoked in the sense of taste, or gustation, particularly during ontogeny when fishes are subject to different environmental variables, remain poorly studied. This review paper focusses on current knowledge to show how plastic and resistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 213 publications
(322 reference statements)
1
45
0
Order By: Relevance
“…He also pointed out that the main branches of the RLA carry only gustatory/taste fibers. As described above, the polynemid RLA-OP + SV2 branches run along the entire length of each pectoral filament, and small protuberances with an external opening that clearly correspond to terminal buds [56][57][58] were visible through scanning electron microscopy on the latero-dorsal surface region of the filament of some examined species (Fig. 9).…”
Section: Discussionmentioning
confidence: 66%
“…He also pointed out that the main branches of the RLA carry only gustatory/taste fibers. As described above, the polynemid RLA-OP + SV2 branches run along the entire length of each pectoral filament, and small protuberances with an external opening that clearly correspond to terminal buds [56][57][58] were visible through scanning electron microscopy on the latero-dorsal surface region of the filament of some examined species (Fig. 9).…”
Section: Discussionmentioning
confidence: 66%
“…The relationships among environment, the feeding habits and the morphology and the consequent functions of the oral cavity and especially of the tongue are well known. Recent studies demonstrated the effects of environment on the taste system adaptability in fishes with special regard to the effects of pollution and contaminants (Kasumyan, 2019). The Atlantic salmon is one of the most farmed fish in the world by aquaculture, and in the last years, the world salmon farmers produce 2.5 million tonnes of salmon annually.…”
Section: Discussionmentioning
confidence: 99%
“…An important role by different hormones in feeding, related to the morphological characteristics, has been recently demonstrated in the digestive system in teleosts (Audira et al., 2018; Carnovali, Luzi, Terruzzi, Banfi, & Mariotti, 2018; Mania et al., 2017; Montalbano et al., 2016, 2018). The most of the functional processes inside the oral cavity are carried out by the tongue, whose presence and description have been showed in different species of fish, demonstrating the variation in the presence of anatomical structures like taste buds, mucous cells and teeth in teleosts, also of commercial interest (Abbate et al., 2006,2017,2020a,2020b; Abbate, Guerrera, Montalbano, Ciriaco, et al., 2012; Abbate, Guerrera, Montalbano, De Carlos, et al., 2012; Alsafy, Bassuoni, & Hanafy, 2018; Amato et al., 2012; Dos Santos, Arantes, Santiago, & Dos Santos, 2015; El Bakary, 2014; Elgendy, Alsafy, & Tanekhy, 2016; Germanà et al., 2009; Guerrera et al., 2015; Ikpegbu, Ibe, & Nlebedum, 2019; Kasumyan, 2019; Kettratad, Senarat, Boonyoung, & Jiraungkoorsku, 2017; Levanti et al., 2017; Mahmoud, Essa, & Sayed, 2016; Sadeghinezhad, Rahmati‐holasoo, Fayyaz, & Zargar, 2015; Sayed, Mahmoud, & Essa, 2019; Yu et al., 2019). Several significant papers, important as comparative data, are present in the literature in upper vertebrates like birds, reptiles and mammals (Abbate et al, 2008, 2009, 2010, 2020b; Abumandour & Kandyel, 2020; Barbosa et al., 2020; Bels et al., 2020; Cizek, Hamouzova, Goździewska‐Harłajczuk, Klećkowska‐Nawrot, & Kvapil, 2020; Cizek, Hamouzova, Kvapil, & Kyllar, 2019; Emura, 2016a,2016b,2016c,2017,2018a,2018b,2018c,2018d,2019; Erdoğan & Alan, 2012; Erdoğan & Iwasaki, 2014…”
Section: Introductionmentioning
confidence: 99%